Hipertrofi Ventrikel Kiri Disertai Dengan Pembesaran Diameter Osteum Vena Pulmonal - Radityo Prakoso; Erika Maharani; Mohammad Syaifur Rohman; Budiyanto Nagawidjaja; Yoga Yuniadi (The Indonesian Heart Association, 2007)
Background:Hypertensive heart disease, characterized with left ventricular hypertrophy (LVH), which is usually accompanied with left ventricular dysfunction, is prevalent in the community and associated with increased of ostial pulmonary vein diameter. We investigate pulmonary vein diameter in its relationship to left ventricular hypertrophy.Methods and Results: Ostial pulmonary veins divided into four parts, left superior (LS), right superior (RS), left inferior (LI), and right inferior (RI), were assessed by spiral multisliced computed tomography (MSCT) in 46 sinus rhythm subjects. LVH was analyzed by measuring the thickness of interventricular septum by MSCT. There were 23 patients with LVH, and the rest were normal. According to Pearson correlation analysis, we found a significant positive correlation between the degree of LVH and ostial diameter of RS, RI, and LS (p<0.05).Conclusion:Left ventricular hypertrophy is associated with right superior, right inferior and left superior pulmonary veins dilatation.